Strategi Pengelolaan Ekosistem Mangrove di Pulau Kaledupa, Kabupaten Wakatobi - Agusrinal Agusrinal; Muhsin Muhsin; L.O.A Parman Rudia (University of Halu Oleo, 2020)
The mangrove ecosystem is one of the natural resources that is the target of conservation, from the various potential natural resources that exist in the Wakatobi National Park. Mangrove ecosystems support biodiversity conservation, by providing shelter, breeding grounds, nursery, and feeding grounds for various types of animals including several groups of animals that are threatened with extinction, from reptiles, amphibians, aves, and mammals. Mangrove ecosystems can also protect coral reef ecosystems and seagrass. The aim of this research was to analyze the composition and diversity of mangrove species and to formulate a mangrove ecosystem management strategy in Kaledupa Island. This study uses a vegetation analysis method and a SWOT analysis. The results of vegetation analysis showed that there were eight species of mangroves on Kaledupa Island which were divided into four families. These species of mangroves are Avicennia marina, Xylocarpus granatum, Bruguiera gymnorrhiza, Ceriops decandra, Ceriops tagal, Rhizophora apiculata, Rhizophora mucronata, and Sonneratia alba. The highest and lowest mangrove species diversity indexes in Kaledupa Island were shown by the weaning and seedling strata, respectively with values 1,86 and 1,66. Based on the results of the SWOT analysis, mangrove ecosystem management strategies were formulated, namely (1) utilizing the status of the mangrove ecosystem as a conservation area and the existence of strict regulations to preserve mangroves so that they have the potential to become attractive ecotourism areas and (2) empower communities to provide mangrove seeds through the establishment of a nursery so that rehabilitation is no longer hampered by the reason that there are no seeds that are ready for planting.Abstrak Ekosistem mangrove merupakan salah satu jenis sumberdaya alam yang menjadi target konservasi, dari berbagai potensi sumberdaya alam yang ada di kawasan Taman Nasional Wakatobi. Ekosistem mangrove mendukung konservasi keanekaragaman hayati, dengan menyediakan tempat tinggal, tempat berkembang biak, tempat pengasuhan anak dan tempat mencari makan berbagai jenis hewan, termasuk beberapa golongan hewan yang terancam kepunahan, mulai dari golongan reptil, amphibi, aves, dan mamalia. Ekosistem mangrove dapat juga melindungi ekosistem terumbu karang (coral reefs), dan padang lamun (sea grass). Tujuan penelitian ini adalah untuk menganalisis komposisi dan keanekaragaman jenis mangrove serta merumuskan strategi pengelolaan ekosistem mangrove di Pulau Kaledupa. Penelitian ini menggunakan metode analisis vegetasi dan analisis SWOT. Hasil analisis vegetasi menunjukkan bahwa terdapat delapan jenis mangrove di Pulau Kaledupa yang terbagi ke dalam empat famili. Jenis mangrove tesebut adalah Avicennia marina, Xylocarpus granatum, Bruguiera gymnorrhiza, Ceriops decandra, Ceriops tagal, Rhizophora apiculata, Rhizophora mucronata, dan Sonneratia alba. Indeks keanekaragaman jenis mangrove tertinggi dan terendah di Pulau Kaledupa ditunjukkan masing-masing oleh strata sapihan dan semai dengan nilai 1,86 dan 1,66. Berdasarkan hasil analisis SWOT, dirumuskan dua strategi pengelolaan ekosistem mangrove yaitu (1) memanfaatkan status ekosistem mangrove sebagai daerah konservasi dan adanya regulasi yang ketat untuk menjaga kelestarian mangrove sehingga berpotensi untuk dijadikan daerah ekowisata yang menarik dan (2) memberdayakan masyarakat untuk menyediakan bibit mangrove melalui pembentukan kebun bibit sehingga rehabilitasi tidak terhambat lagi dengan alasan tidak tersedianya bibit yang siap tanam.